The Effect of L-Carnitine Use on Some Blood Parameters, Milk Yield, Milk Composition, and Live Weight in the Transition Period of Dairy Cows - Atlay, Hasan; Gülşen, Hatice Kübra (Journal of the Hellenic Veterinary Medical Society, 2022)
This study aims to determine the effect of supplementing L-carnitine during the transition period on fatty liver, ketosis and milk yield of dairy cows. The control group includes ten cows fed with normal ration (n=10), while the experimental group consists of 11 cows daily supplemented with six-grams of rumen-protected L-carnitine additive orally (n=11). In the study, while there is no statistically significant difference between serum NEFA and BHBA levels between the control group and the experimental group treated with carnitine, the difference in glucose level is statistically significant (p <0.001) in terms of time. While a severe decrease in glucose levels occurs in the control group after birth, the group given carnitine remains within the normal range. The carnitine-treated group’s serum BUN value is significantly lower than the control group (p <0.05). Accordingly, L-carnitine neither has a statistically significant effect on Ca, P, GGT, triglyceride values, nor milk yield, milk composition, and live weight. In conclusion, daily oral administration of 6 g L-carnitine increases the use of fatty acids in energy metabolism through the intake into tissues and decreases muscle protein catabolism.